Lower Limb Somatosensory Discrimination Is Impaired in People With Parkinson's Disease: Novel Assessment and Associations With Balance, Gait, and Falls. Issue 7 (5th September 2019) - Gorst, Terry; Marsden, Jonathan; Freeman, Jenny
ABSTRACT: Background: People with Parkinson's disease (PD) have often compromised walking and balance. This may be the result of the impaired lower limb tactile and proprioceptive sensation. Existing clinical measures may not be sufficiently sensitive to uncover these sensory impairments. Objective: To determine whether novel measures of lower limb somatosensory discrimination are psychometrically robust and associated with mobility outcomes in people with PD. Methods: Lower limb somatosensation was assessed on 2 occasions, 3 to 7 days apart, using the following 3 novel tests: gradient discrimination, roughness discrimination, and step height discrimination. Static and dynamic balance (Brief Balance Evaluations Systems Test), falls incidence, falls confidence (Falls Efficacy Scale), and gait (speed and step length) were also obtained. The participants were 27 people with PD and 27 healthy controls. Results: Novel tests showed good to excellent intrarater reliability (intraclass correlation coefficient = 0.72–0.92). Significantly higher gradient and step height discrimination thresholds ( P < 0.01) were demonstrated in the participants with PD when compared with the healthy controls, indicating worse position sense at the ankle, knee, and hip. Significant correlations were identified between gradient discrimination and falls incidence ( r = 0.55), falls confidence ( r = 0.44), and balance ( r = 0.63), but not gait ( r = 0.21). Step height discrimination was significantly correlated with balance ( r = 0.54). Foot roughness discrimination was not significantly different between people with PD and healthy controls and was not significantly correlated with mobility measures ( P > .05). Conclusion: These novel tests are psychometrically robust and identify impaired lower limb position sense, which was associated with balance and falls in this sample of PD patients. Interventions targeting somatosensory processing in PD may improve aspects of balance and reduce falls risk. Further research is warranted.